(untitled) (Research, Society and Development, 2020)
Objective: This study aims to analyze the profile of maternal mortality in the state of Amapá during the years 2012 to 2016. Methods: This is a descriptive study with data analysis from the Mortality Information System and Birth Information System Alive, performing the Maternal Mortality Ratio (MMR). Results: In the period, there was a variation in the MMR from 49 to 111 deaths per 100,000 live births. It was observed that 52.8% of deaths were in the puerperium; 100% were classified as preventable; at the hospital (90.7%). The age group from 30 to 39 years old, 43.1%, women with completed high school, 34.0%, single, 53.4%, and brown, 67.2%, predominated. Conclusion: Maternal mortality has an increasing profile in the state, evidenced by black women (black and brown), aged 30 to 39, single, with complete high school, whose death is due to preventable and direct causes, in cesarean deliveries, in the hospital environment. The profile allows the orientation of management work, the care of health professionals and the actions of civil society.